2019
DOI: 10.1021/acs.jpcc.9b05680
|View full text |Cite
|
Sign up to set email alerts
|

Implications of the Interface Modeling Approach on the Heat Transfer across Graphite–Water Interfaces

Abstract: In this investigation, the thermal transport across graphite−water interfaces was studied by means of nonequilibrium classical molecular dynamics (NEMD) simulations. The main focus of this work was the assessment of the interface modeling approach of the nonbonded interactions, where empirical models optimized for predicting an experimental wetting condition were compared against interface models derived from multibody electronic structure methods. To understand the mechanisms involved in the interfacial heat … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 77 publications
2
18
0
Order By: Relevance
“…Contrary to the hydrophilic surface of polyelectrolyte-coated glass, graphene-coated glass is highly hydrophobic , and therefore a higher R K resistance is expected between the water and the hydrophobic graphene-coated glass. Moreover, very high values of R K between graphene and SiO 2 interfaces have been measured, including a dramatically five-order of magnitude increase in R K when the graphene is not in full contact with glass but presents some corrugation of nm-sized height.…”
Section: Resultsmentioning
confidence: 99%
“…Contrary to the hydrophilic surface of polyelectrolyte-coated glass, graphene-coated glass is highly hydrophobic , and therefore a higher R K resistance is expected between the water and the hydrophobic graphene-coated glass. Moreover, very high values of R K between graphene and SiO 2 interfaces have been measured, including a dramatically five-order of magnitude increase in R K when the graphene is not in full contact with glass but presents some corrugation of nm-sized height.…”
Section: Resultsmentioning
confidence: 99%
“…If the interplay between atomic topography and energy of interaction permits the water molecules to concentrate and get closer or even infiltrate past the outermost layer of solid atoms, the in-plane vibrations are enhanced. Alternatively, the out-of-plane modes show larger contributions for interfaces featuring flatter energy landscapes, larger solid–liquid equilibrium distances, or low interfacial liquid concentration, which are the result of large repulsion regions near the substrate, i.e., graphite, silicon carbide (SiC), and silicon (Si) in the (111) orientation. ,, The composition of q S–L (ω) can be correlated with the interfacial entropy calculations in Figure a. Low Δ S SL , associated with a small bulk-to-interface water structuring change, indicates that interfacial water molecules experienced a smoother energy landscape, thus a prohibitive path for in-plane-mode dominant heat transfer.…”
Section: Resultsmentioning
confidence: 91%
“…These results echo those found for heat transfer across solid−liquid interfaces, a different interfacial transport property, for different solid substrates. 31,33,86 These aforementioned findings also reflect a poor description of the interfacial heat transfer as a function of the surface wettability, which then is improved drastically by considering the liquid depletion length. In both cases, δ quantifies the availability of interfacial carriers, of energy for heat transfer, and momentum for hydrodynamic slip.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…On the wettability side of the theory, scaling functions between L s and the contact angle (θ) and between L s and the density depletion length (δ) have been reported in the literature. As a related topic, investigations on thermal transport across solid–liquid interfaces have shown that relationships based on wettability do not provide a consistent description of the thermal boundary conductance, while relations using the interfacial liquid structuring (δ) were able to describe the behavior of the interfacial energy transport. Therefore, it is necessary to carefully address the applicability of describing hydrodynamic slip using wettability and interfacial liquid properties. Nevertheless, evidence indicates that the explanation for the physics governing the hydrodynamic slip is concealed behind the physical characteristics of the solid–liquid interface.…”
Section: Introductionmentioning
confidence: 99%